2020
DOI: 10.1007/s11306-020-01653-7
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics analyses in non-diabetic middle-aged individuals reveal metabolites impacting early glucose disturbances and insulin sensitivity

Abstract: Introduction Several plasma metabolites have been associated with insulin resistance and type 2 diabetes mellitus. Objectives We aimed to identify plasma metabolites associated with different indices of early disturbances in glucose metabolism and insulin sensitivity. Methods This cross-sectional study was conducted in a subsample of the Leiden Longevity Study comprising individuals without a history of diabetes mellitus (n = 233) with a mean age of 63.3 ± 6.7 years of which 48.1% were men. We tested for assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…According to recent studies, it has been found that there is a strong association between the chronic elevation of BCAA in serum and insulin resistance ( 32 , 33 ). In a study of serum metabolites based on non-diabetic middle-aged people ( 34 ), serum tryptophan and tyrosine concentrations are found to be related to glucose intolerance and insulin resistance, and these two amino acids are also higher in patients with diabetics with decreased insulin secretion ( 34 , 35 ). Serum L-homocysteine concentrations are also associated with insulin resistance and diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…According to recent studies, it has been found that there is a strong association between the chronic elevation of BCAA in serum and insulin resistance ( 32 , 33 ). In a study of serum metabolites based on non-diabetic middle-aged people ( 34 ), serum tryptophan and tyrosine concentrations are found to be related to glucose intolerance and insulin resistance, and these two amino acids are also higher in patients with diabetics with decreased insulin secretion ( 34 , 35 ). Serum L-homocysteine concentrations are also associated with insulin resistance and diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…DC. C4.OH, [ 28 ] Pre-diabetes GC–MS Tyrosine, lysine, alanine, valine, proline, phenylalanine, tryptophan, hexadecanoic acid, alpha-ketoglutaric acid, myristic acid, octadecanoic acid, uric acid [ 29 ] Pre-diabetes and T2DM LC-MS Ceramides, saturated sphingomyelins, unsaturated sphingomyelins, hydroxyl-sphingomyelins, and a hexosylceramide [ 30 ] Pre-diabetes LC-MS N2, N2-dimethylguanosine, 7-methylguanine and 3-hydroxytrimethyllysine [ 31 ] Pre-diabetes LC-MS A cluster of saturated sphingomyelins [ 32 ] Pre-diabetes 1H-NMR Lipids in HDL subtypes, citrate, glycoprotein acetyls, branched-chain amino acids, VLDL lipids [ 33 ] Pre-diabetes LC-MS Alanine, aspartate, glutamate, isoleucine, leucine, phenylalanine, tyrosine, tryptophan, and valine [ 34 ] Pre-diabetes GC-MS and LC-MS 1,5-anhydroglucitol [ 35 ] Pre-diabetes HPLC-MRM TAGs, lyso-phosphatidylinositols, phosphatidylcholines, PUFA-PEps, cholesteryl esters [ 36 ] Pre-diabetes CIL-LC-MS Methionine (Met) sulfoxide, amino acids (Asn, Gln, and His), 2-methyl-3-hydroxy-5-formylpyridine-4-carboxylate, L-2-amino-3-oxobutanoic acid, serotonin, and 4,6-dihydroxyquinoline. [ 37 ] Pre-diabetes GC-MS and LC-MS Lysophosphatidylcholines (muscle), glycodeoxycholic acid (liver) …”
Section: Application Of Metabolomics In the Diagnosis Of T2dmmentioning
confidence: 99%
“… [ 37 ] Pre-diabetes GC-MS and LC-MS Lysophosphatidylcholines (muscle), glycodeoxycholic acid (liver) [ 38 ] Pre-diabetes and diabetes GC-MS Maltose, glucose, trehalose, an unknown sugar compound (U15), mannose, fructose, sedoheptulose, and 1,5 anhydroglucitol, [ 39 ] T2DM CIL-LC-MS Amino acids, amino acids metabolites, and dipeptides. [ 37 ] T2DM GC-MS and LC-MS Carnitines (liver), lysophosphatidylcholines (muscle and serum) [ 38 ] T2DM LC-MS Alanine, 3-methyl histidine, glutamic acid, arginine, tryptophan, and ethanolamine sarcosine [ 40 ] T2DM 1H-NMR and 2D-NMR 61 distinct metabolites [ 41 ] Pre-diabetes and diabetes LC-MS Oxidized glycerophosphatidylcholines [ 42 ] Obese insulin sensitive (OIS) LC-MS Phospholipid metabolites, including choline, glycerophosphoethanolamine, and glycerophosphorylcholine [ 43 ] T2DM GC-MS Tyrosine, alanine, valine, tryptophan, and alpha-ketoglutaric acid [ 29 ] T2DM LC-MS Organophosphate flame retardant (OPFR) diesters [ 44 ] T2DM LC-MS …”
Section: Application Of Metabolomics In the Diagnosis Of T2dmmentioning
confidence: 99%
See 1 more Smart Citation
“…(5) The application of metabolomics in observational epidemiological studies has helped to identify metabolites involved in the pathogenesis of T2D, or that might contribute to T2D incidence. (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16) For example, a recent meta-analysis identified associations of incident T2D with differences in several lipid and non-lipid metabolites, including higher levels of branched chain amino acids (BCAAs), some fatty acids and acylcarnitines, amongst others. (17) For CAD, metabolomics in observational studies has helped to identify key metabolic characteristics of the disease, (18)(19)(20)(21)(22)(23)(24)(25) to predict and diagnose CAD, (26)(27)(28)(29) and to predict outcomes and mortality in CAD patients.…”
Section: Introductionmentioning
confidence: 99%